Structural characteristics of silica sonogels prepared with additions of isopropyl alcohol - Donatti, D. A.; Ruiz, A. Ibanez; Kumakawa, M. M.; Vollet, D. R. (Amer Chemical Soc, 2006)
Wet silica gels with similar to 1.4 x 10(-3) mol SiO2/cm(3) and similar to 92 vol% liquid phase were obtained from sonohydrolysis of tetraethoxysilane (TEOS) with different additions of isopropyl alcohol ( IPA). The IPA/TEOS molar ratio R was changed from 0 to 4. Aerogels were obtained by supercritical CO2 extraction. The samples were analyzed by small-angle X-ray scattering (SAXS) and nitrogen adsorption. The wet gels exhibit mass fractal structure with fractal dimension increasing from D similar to 2.10 to D similar to 2.22, characteristic length xi decreasing from similar to 9.5 to similar to 6.9 nm, as R increases from 0 to 4, and an estimated characteristic length for the primary silica particles lower than similar to 0.3 nm. The supercritical process apparently eliminates a fraction of the porosity, increasing the mass fractal dimension and shortening the fractality domain in the mesopore region. The fundamental role of isopropyl alcohol on the structure of the resulting aerogels is to decrease the porosity and the pore mean size as R changes from pure TEOS to R = 4. A secondary structure appearing in the micropore region of the aerogels can be described as a mass/surface fractal structure, with correlated mass fractal dimension D-m similar to 2.7 and surface fractal dimension D-s similar to 2.3, as inferred from SAXS and nitrogen adsorption data.